The Central Engine of Low-luminosity Radio Galaxy 3C 270 (NGC 4261) - Chengzhang Jiang; Robert Antonucci; J. A. Acosta-Pulido; Patrick Ogle (The Astrophysical Journal)
We present the polarization spectra of the nucleus of 3C 270. We confirm that the polarization angles of both the continuum and the emission lines are close to perpendicular to the jet direction after careful correction of interstellar polarization, which indicates polar scattering. The Stokes flux spectrum resembles the total flux spectrum, with no need for a broad component from the broad-line region. Over 94% of a sample of Seyfert I broad-line profiles would be significantly detected if present in our polarized flux spectrum. We favor the hypothesis that we are observing the continuum including any contribution from radiatively inefficient accretion flow and beamed synchrotron instead of a big blue bump, as well as the innermost narrow-line region, through reflection. This makes 3C 270 the third known case, after NGC 4258 and Centaurus A, where only narrow lines (and the continuum, if present) are scattered, with no evidence of an underlying big blue bump.